Imaging spectroscopy (hyperspectral remote sensing) in southern Africa: an overview - O. Mutanga; J. van Aardt; L. Kumar (South African Journal of Science)
Recent developments in imaging spectroscopy have seen a dramatic improvement in the characterisation of terrestrial features due to the high spectral resolution of the sensors used. For example vegetation species discrimination, stress detection and foliar chemistry mapping can now be achieved using these high spectral resolution sensors, a task that was almost impossible with coarse resolution satellite sensors. In spite of its capabilities, imaging spectroscopy is still in its early stages of development and application in southern Africa. This overview will attempt to briefly describe the science and analysis techniques, as well as review trends and challenges in the South African imaging spectroscopy landscape. It therefore is not intended as a pure research paper, but merely to illustrate the potential of and developments in imaging spectroscopy. This is pertinent to the South African scientific community where the technology is still in its infancy, especially given that the first-ever spaceborne South African imaging spectrometer, the Multi-Sensor Micro-Satellite Imager Satellite (MSMISat) is being developed for launch in the near future.